Lyapunov Center Theorem of Infinite Dimensional Hamiltonian Systems (Analysis in Theory and Applications, 2021)
In this paper we reformulate a Lyapunov center theorem of infinite dimensional Hamiltonian systems arising from PDEs. The proof is based on a modified KAM iteration for periodic case.